A composite composition. - Abdullah, Luqman Chuah; Khalid, Mohammad; Md. Tahir, Paridah; Ratnam, Chantara Thevy (2010)

(untitled)
The present invention relates to a composite composition that is useful in the manufacture of a thermoplastic product having improved physical and mechanical properties. Accordingly, the composition of the present invention comprises a mixture of organic filler which consists of a cellulosic material derived from a fibrous animal biomass and a coupling agent which consists of maleic anhydride grafted polypropylene, in which the mixture is capable of being reinforced in a polymer which includes polypropylene, polyethylene and polystyrene.